Prognostic factors and the new ways of treatment in neuroblastoma - Adamkiewicz-Drożyńska, Elżbieta (Contemporary Oncology/Współczesna Onkologia, 2000)
The study presents a review of informations concerning prognostic factors in neuroblastoma and currently descovered possibilities of treatment in this children’s neoplasm. Particullary important are currently discovered genetic markers (del 1p, amp N-myc, DDX1) and molecular markers (adhesion, angiogenesis, differentiation markers, other superficial markers and cytokin’s receptors) which allow to estimate agressivity of neoplasm and help to choose adequate outline and proper intensity of therapy. Discusion of various groups of prognostic factors was supplemented by information about the new explorated, hopeful methods of treatment that are examined nowadays.